Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3126/nje.v9i3.25805
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death and kidney health related problems among Nepali migrant workers in Malaysia

Abstract: This paper reports on a consultation meeting that discussed two emerging health issues of Nepali migrant workers in Malaysia and the ways they can be addressed. Primarily, it focused on the issue of sudden cardiac deaths of Nepali migrant workers in Malaysia. This issue has been raised internationally by both scientific and media in the recent years. Secondly, it discussed kidney health related problem among Nepali migrant workers which has caught the attention of Nepali media recently. The meeting was organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…10,11 The Nepali Embassy in a key migrant destination country also acknowledges the rising cases of kidney-related problems among migrant workers. 18 Our findings also support this as nearly two-thirds of the respondents had ever treated migrant patients who were returned to Nepal only due to kidney-related problems. As patients show no symptoms, kidney-related problems are hard to diagnose in the early stages.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…10,11 The Nepali Embassy in a key migrant destination country also acknowledges the rising cases of kidney-related problems among migrant workers. 18 Our findings also support this as nearly two-thirds of the respondents had ever treated migrant patients who were returned to Nepal only due to kidney-related problems. As patients show no symptoms, kidney-related problems are hard to diagnose in the early stages.…”
Section: Discussionsupporting
confidence: 80%
“…The kidney health risk of low-skilled male migrant workers from Asia in the countries of the GCC and Malaysia are beginning to draw scientific attention. 18 A longitudinal study among Indian construction workers in Saudi Arabia suggested that exposure to heat stress, long working hours, dehydration, sleep deprivation, and obesity may induce the risk to kidney health in workers. 19 In Ponorogo district of Indonesia, 18% of the patients with chronic renal failure were former migrant workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, nearly 70%, 50%, and 80% of the total population of Qatar, Bahrain, and UAE are migrants, respectively ( Kristiansen & Sheikh, 2014 ). Similarly, in some Southeast Asian countries such as in Malaysia, one fourth of the migrants are Bangladeshi people ( Aryal et al, 2019 ). In various Asian countries, specifically in the Middle Eastern countries, there is a massive demand for migrant workers; therefore, a large number of foreign workers migrate every year to chase their dreams to improve their domestic economy and quality of life ( Weeraratne, 2020 ).…”
mentioning
confidence: 99%